Effects of high fat versus high carbohydrate diets on plasma lipids and lipoproteins in endurance athletes - Brown, R. C.; Cox, C. M. (Medicine & Science in Sports & Exercise, 1998)
PURPOSE AND METHODS: Recent research suggesting the performance benefits of high fat diets for endurance athletes have been viewed with caution because of the potential negative health consequences, including increased coronary heart disease risk. This study examined the effects of a high fat (HF: 50% of total energy from fat, 37% carbohydrate) versus a high carbohydrate (HC: 15% of total energy from fat, 69% carbohydrate) diet on plasma lipids and lipoproteins in 32 endurance trained cyclists over a 3-month period. Plasma total, low density lipoprotein (LDL), high density lipoprotein (HDL), HDL2 and HDL3 cholesterol, triglycerides, apolipoprotein A1, and hematocrit (Hct) were measured at baseline and after weeks 4, 8, and 12. RESULTS: Changes in lipids and lipoproteins from baseline to week 12 did not differ between the two groups except for triglycerides, which increased significantly from 1.04 +/- 0.17 mmol.L-1 to 1.28 +/- 0.31 mmol.L-1 in HC (P = 0.012). The only significant changes that occurred within each group from baseline to week 12 was the significant increase in total cholesterol and triglycerides in HC. Body composition changes did not differ between the two groups from baseline to week 12 as measured by dual x-ray absorptiometry. CONCLUSIONS: During periods of endurance training when energy requirements are high, increasing the percentage of fat in the diet to approximately 50% of total energy did not result in adverse changes to the plasma lipoprotein profiles of this group of athletes.